2011
DOI: 10.1016/j.pediatrneurol.2010.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Language Pathway in Children With Angelman Syndrome

Abstract: Angelman Syndrome is a genetic disorder characterized by pervasive developmental disability with failure to develop speech. We examined the basis for severe language delay in Angelman Syndrome patients using diffusion tensor imaging. Magnetic Resonance Imaging/diffusion tensor imaging was performed in seven genetically confirmed Angelman Syndrome children (age:70±26 months, five males) and four age-matched controls to investigate the microstructural integrity of arcuate fasciculus and other major association t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 25 publications
5
36
0
Order By: Relevance
“…Dendrites in layer III and V neurons of the visual cortex are shorter, less complex, and have fewer spines [176]. MRI and diffusion tensor imaging studies have revealed impaired white matter integrity in subjects with Angelman’s syndrome [281, 354, 388], likely due to a delay in myelination [146]. Similar to the observation of small brain size in human samples from Angelman’s syndrome, the total brain weight, as well as the weight of the cortex and cerebellum, is lower in a mouse model with maternal Ube3a deleted ( Ube3a m−/p+ ) [181].…”
Section: Lessons From Animal Modelsmentioning
confidence: 99%
“…Dendrites in layer III and V neurons of the visual cortex are shorter, less complex, and have fewer spines [176]. MRI and diffusion tensor imaging studies have revealed impaired white matter integrity in subjects with Angelman’s syndrome [281, 354, 388], likely due to a delay in myelination [146]. Similar to the observation of small brain size in human samples from Angelman’s syndrome, the total brain weight, as well as the weight of the cortex and cerebellum, is lower in a mouse model with maternal Ube3a deleted ( Ube3a m−/p+ ) [181].…”
Section: Lessons From Animal Modelsmentioning
confidence: 99%
“…Diffusion tensor tractography (DTT), derived from DTI, allows for three-dimensional reconstruction and estimation of the AF (Catani et al, 2005; Nucifora et al, 2005; Glasser and Rilling, 2008). Therefore, DTI has been employed in many studies for evaluation of the AF in various brain pathologies, including stroke (Yamada et al, 2007; Breier et al, 2008, 2011; Hosomi et al, 2009; Rauschecker et al, 2009; Schlaug et al, 2009; Zhang et al, 2010; Kim et al, 2011; Kwon and Jang, 2011; Marchina et al, 2011; Song et al, 2011; Wilson et al, 2011; Kim and Jang, 2013; Kummerer et al, 2013; Yeatman and Feldman, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…In an effort to relate brain anatomy to clinical phenotype in AS, our group(Wilson BJ et al, 2010; Wilson BJ et al, 2011)and subsequently others(Peters et al, 2011) have studied the major brain tracts using diffusion tensor imaging (DTI) with tractography and have shown very consistent abnormalities in various cortical association tracts, including the arcuate fasciculus thus accounting for the virtual absence of speech in these individuals.…”
Section: Introductionmentioning
confidence: 99%